2011
DOI: 10.5194/bg-8-489-2011
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of ocean color model estimates of marine primary productivity in coastal and pelagic regions across the globe

Abstract: Nearly half of the earth’s photosynthetically fixed carbon derives from the oceans. To determine global and region specific rates, we rely on models that estimate marine net primary productivity (NPP) thus it is essential that these models are evaluated to determine their accuracy. Here we assessed the skill of 21 ocean color models by comparing their estimates of depth-integrated NPP to 1156 in situ 14C measurements encompassing ten marine regions including the Sargasso Sea, pelagic North Atlantic, coastal No… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(117 citation statements)
references
References 33 publications
2
113
0
2
Order By: Relevance
“…Previous primary production intercomparison exercises matched in situ carbon uptake rates with NPP estimated mostly from ocean color models (OCMs) [e.g., Balch et al, 1992;Campbell et al, 2002;Saba et al, 2011] and, more recently, from some coupled biogeochemical ocean general circulation models (BOGCMs) [Carr et al, 2006;Friedrichs et al, 2009;Saba et al, 2010] in various regions of the ocean except the Arctic Ocean. Popova et al [2012] and Vancoppenolle et al [2013] reported the results from various BOGCMs and Earth System Models (ESMs) that were compared for the Arctic domain against satellite-derived NPP albeit with known issues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous primary production intercomparison exercises matched in situ carbon uptake rates with NPP estimated mostly from ocean color models (OCMs) [e.g., Balch et al, 1992;Campbell et al, 2002;Saba et al, 2011] and, more recently, from some coupled biogeochemical ocean general circulation models (BOGCMs) [Carr et al, 2006;Friedrichs et al, 2009;Saba et al, 2010] in various regions of the ocean except the Arctic Ocean. Popova et al [2012] and Vancoppenolle et al [2013] reported the results from various BOGCMs and Earth System Models (ESMs) that were compared for the Arctic domain against satellite-derived NPP albeit with known issues.…”
Section: Introductionmentioning
confidence: 99%
“…Visible spectral radiometric data are used widely to assess water productivity (Saba et al, 2011) and to study effect of climate change on ocean productivity (Behrenfeld et al, 2006). Optical scanners of Sea-viewing Wide Field-of-view Sensor (SeaWiFS), MEdium Resolution Imaging Spectrometer (MERIS), Moderate Resolution Imaging Spectroradiometer aboard the Terra and Aqua satellites (MODIS-Aqua/Terra) measure water leaving radiance at several spectral bands (R RS ) (Feldman and McClain, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore focused only on open ocean areas of the Black Sea (see Fig.1 for further details) where the errors in SeaWiFS Chl-a are likely to be small due to low or minimal TSM and aCDOM. We also deployed one of the most accurate PP satellite models based on recent NASA inter-comparisons (Carr et al 2006;Saba et al 2011).…”
Section: Discussion Temporal Trends In Chl-a and Ppmentioning
confidence: 99%
“…PPWRM was calculated as follows: (1) This model has proved to be the most accurate satellite PP model for the Atlantic Ocean where modelled values are within 20% of in situ (Tilstone et al, 2009). During recent NASA PP intercomparisons, Carr et al (2006) and Saba et al (2011) found that this model was the most accurate in eight out of ten regions of the global ocean and within ~30% of in situ values.…”
Section: Primary Productionmentioning
confidence: 99%